2013
DOI: 10.1111/ijn.12204
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self‐compassion and emotional intelligence in nursing students

Abstract: Nursing focuses on meeting physical, social and emotional health-care needs of individuals, families and society. In health care, nurses directly communicate with patients and try to empathize with them. Nurses give care under emotionally intense conditions where the individual undergoes pain and distress. Research is aimed at analysing the correlation of self-compassion and emotional intelligence of nursing students. The population of the research consisted of all the undergraduate students (571 students) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 20 publications
2
35
2
2
Order By: Relevance
“…[19] investigated the correlation of self-compassion and EI of nursing students using self-compassion and EI Assessment Scales. The results showed a correlation between self-compassion and EI, which suggested that these two characteristics should be developed among nursing students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] investigated the correlation of self-compassion and EI of nursing students using self-compassion and EI Assessment Scales. The results showed a correlation between self-compassion and EI, which suggested that these two characteristics should be developed among nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the development of self-compassion and EI in nursing students is imperative. [19]…”
Section: Introductionmentioning
confidence: 99%
“…Barkhordari ve Rostambeygi [8] tarafından hemşirelik birinci ve son sınıf öğrencilerinin duygusal zeka düzeyleri arasında fark olmadığı görülmüş, bu sonuç doğrultusunda hemşirelik eğitim müfre-datlarında DZ üzerinde durulması gerektiği belirtilmiştir. Hemşirelik öğrencilerinin DZ düzeyleri ile bakım davranışları, dayanıklılıkları [17] ve şefkat duyguları [18] arasında pozitif yönde bir ilişki olduğunu gösteren çalışma sonuçlarına rastlanmaktadır. Ayrıca DZ'nın hemşirelerin başetme mekanizmalarının yönetim tarzları ve performansları üzerinde olumlu etkilerinin olduğu da görülmektedir.…”
unclassified
“…The same findings were reported by [46] who concluded that nursing students had fair emotional intelligence. Moreover, [47] specified that that nursing students had a moderate level of emotional intelligence. Besides, the study results parallels to [48] who found that moderate to high levels of emotional intelligence among nurses, and high levels of caring behavior reflect on patient satisfaction and desire to come back to these hospitals.…”
Section: Discussionmentioning
confidence: 99%